THE IMPLEMENTATION OF LEARNING MEDIA BASED ON ICT IN MATHEMATICAL LEARNING PROCESS IN ELEMENTARY SCHOOL - Wahida Amalia (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2018)
In order for the presentation of the material presented by the teachers more effectively and efficiently. Therefore it needs media learning that can motivate and stimulate students to morale in learning. One of them is by making use of ICT-based learning or media that we often call it TIK. This research aims to describe how the implementation of ICT-based learning media in the process of learning mathematics inprimary school (elementary school). This research is a research library. the nature of this research is descriptive-i.e. decomposition analysis on a regular basis, then the whole concept of giving of the comprehension and explanation to taste the result description. The analysis of the data used in this study is the analysis of the content (content analysis). The results of the research study this library is; (1) the existence of the benefits of ICT-based learning media in the field of education; (2) the existence of the benefits of ICT-based learning media in the process of learning mathematics in primary school (elementary school).